UNIT PENUNJANG AKADEMIK LINGKUNGAN LAHAN BASAH UNIVERSITAS LAMBUNG MANGKURAT - Arina Ahyan Nazhifa; Naimatul Aufa (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
Mangrove wetlands play a crucial role in maintaining ecosystem balance, climate mitigation, and coastal community welfare, particularly in the 611-hectare area managed by the UPA Wetland Environment at Lambung Mangkurat University in South Kalimantan for integrating conservation, research, and education. This study aims to design sustainable facilities using biomimicry that mimics natural mangrove adaptations, producing adaptive buildings with minimal intervention per the Ramsar Convention. Zoning methods cover conservation, research, and education with nursery plants, observation towers, researcher cottages, coworking spaces, exhibitions, and community workshops. Results yield functional facilities supporting ecological preservation; conclusion: this innovative model is recommended for national mangrove rehabilitation to empower local communities.